Golgi, trafficking, and mitosis dysfunctions in pulmonary arterial endothelial cells exposed to monocrotaline pyrrole and NO scavenging - Lee, Jason (American Physiological Society, 2009)
Although the administration of monocrotaline (MCT) into experimental animals is in widespread use today in investigations of pulmonary arterial hypertension (PAH), the underlying cellular and subcellular mechanisms that culminate in vascular remodeling are incompletely understood. Bovine pulmonary arterial endothelial cells (PAECs) in culture exposed to monocrotaline pyrrole (MCTP) develop “megalocytosis” 18–24 h later characterized by enlarged hyperploid cells with enlarged Golgi, mislocalization of endothelial nitric oxide synthase away from the plasma membrane, decreased cell-surface/caveolar nitric oxide (NO), and hypo-S-nitrosylation of caveolin-1, clathrin heavy chain, and N-ethylmaleimide-sensitive factor. We investigated whether MCTP did in fact affect functional intracellular trafficking. The NO scavenger (4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (c-PTIO) and the NO donor diethylamine NONOate were used for comparison. Both MCTP and c-PTIO produced distinctive four- to fivefold enlarged PAECs within 24–48 h with markedly enlarged/dispersed Golgi, as visualized by immunostaining for the Golgi tethers/matrix proteins giantin, GM130, and p115. Live-cell uptake of the Golgi marker C(5) ceramide revealed a compact juxtanuclear Golgi in untreated PAECs, brightly labeled enlarged circumnuclear Golgi after MCTP, but minimally labeled Golgi elements after c-PTIO. These Golgi changes were reduced by NONOate. After an initial inhibition during the first day, both MCTP and c-PTIO markedly enhanced anterograde secretion of soluble cargo (exogenous vector-expressed recombinant horseradish peroxidase) over the next 4 days. Live-cell internalization assays using fluorescently tagged ligands showed that both MCTP and c-PTIO inhibited the retrograde uptake of acetylated low-density lipoprotein, transferrin, and cholera toxin B. Moreover, MCTP, and to a variable extent c-PTIO, reduced the cell-surface density of all receptors assayed (LDLR, TfnR, BMPR, Tie-2, and PECAM-1/CD31). In an important distinction, c-PTIO enhanced mitosis in PAECs but MCTP inhibited mitosis, even that due to c-PTIO, despite markedly exaggerated Golgi dispersal. Taken together, these data define a broad-spectrum Golgi and subcellular trafficking dysfunction syndrome in endothelial cells exposed to MCTP or NO scavenging.